Combined Effects of Viscous Dissipation and Thermal Radiation on non-Newtonian FluidAlong a Surface with Heat Generation and Uniform Surface Heat Flux (Dhaka University Journal of Science, 2015)
The paper analyses the effects of Magneto-hydrodynamic (MHD) free convective heat and mass transfer flow on non-Newtonian power law fluids along a continuously moving stretching sheet with radiation, heat generation and viscous dissipation under the simultaneous action of suction, thermal radiation, heat source, uniform transverse magnetic field and viscous dissipation. The governing non-linear partial differential equations describing the flow fields under consideration are transformed into non-linear ordinary differential equations by using appropriate analysis of similarity and then solved the resulting problem numerically by applying Nachtsheim-Swigert shooting iterative technique along with sixth order Runge-Kutta integration scheme. The computational results of the skin friction coefficient (Cf) the rate of heat transfer namely the local Nusselt number (Nux) and the mass transfer coefficient namely the local Sherwood number (Shx) have also been presented in tabular form. In the present study, a comparison has also been done with a published article and found a good agreement.Dhaka Univ. J. Sci. 63(2):97-104, 2015 (July)